Hopeful News for Physicians Who Involved in the Treatment of Critical Aluminum Phosphide (Rice Pill) Poisoning Patients. (20th October 2022) - Vafapour, Fatemeh; Sedaghattalab, Moslem
Abstract : Introduction . Aluminum phosphide (rice tablet) was first introduced as a pesticide in India. Rice tablets are commonly used in Iran due to their high efficacy against rodents and insects, low cost, and availability. Aluminum phosphide is a lethal poison without antidote and causes cardiocirculatory collapse and has negative inotropic cardiac effect. Human and animal studies showed that high dose insulin had positive cardiac inotropic effects. GIK (glucose, insulin, and potassium) assists heart uptake of carbohydrates that are the major fuel substrate of the myocard muscle under stressed conditions and leading to correction of acidosis, increased myocardial contractility, and peripheral vascular resistance. Case Presentation . In this manuscript, a young woman with aluminum phosphide poisoning was described to have presented with hypotension, hypoxemia, and severe metabolic acidosis. In contrast to our previous experiences that approximately all rice tablet poisoning patients with shock were dead despite full conservative treatment, this patient miraculously was saved with high dose intravenous regular insulin infusion and was discharged from the hospital with good condition and without any complications. Conclusion . Rice tablet poisoning has high fatality rate, and to date, no antidote is available. GIK is suggested as a potential life saving treatment for critical rice tablet poisoning patients with symptoms and signs of shock.